Problematics of the Legal Settlement of Connective Crimes in Indonesia - Budi Pramono; Pramono, Agung (Hang Tuah Law Journal, 2024)
This research discusses the issue of forming a Joint Decree of the Minister of Defense, Attorney General and Commander of the Indonesian National Army, whether it is in accordance with the provisions of the laws in force in Indonesia. This research falls into the category of normative legal research with a statutory and conceptual approach. The results of the research found that the Minister of Defense, the Attorney General and the Commander-in-Chief have the authority to form a Permanent Team for Investigating Criminal Crimes, but its formation does not involve elements of the Indonesian National Police as investigators of general crimes and certain Civil Servant Investigators as investigators of certain crimes (including Commission investigators). Eradication of Corruption) does not comply with the mechanisms regulated in the Criminal Procedure Code and the Military Justice Law. Conditions like this have the implication of not being able to carry out investigations into general crimes and specific crimes related to connection cases, except for corruption crimes. The issuance of the Joint Ministerial Decree has the implication of creating a statutory law in the process of investigating general crimes in connection cases. In order to fill this statutory law, law enforcers carry out legal smuggling by carrying out a separation process, resulting in the potential for inequality before the law.